STRATEGIES OF INTRODUCING THE INDIVIDUAL LEARNING STYLE IN THE DEVELOPMENT OF THE ENGLISH LANGUAGE LEXICAL COMPETENCE OF PUPILS - Olesia Yehorova; Oleksandra Bila (Vasyl Stefanyk Precarpathian National University, 2018)
The article focuses on the issue of individual learning styles according to the VAK-model within the student-centered approach in education. Considering the necessity of introducing innovative education approaches into Ukrainian educational sphere, the paper highlights the advantages of implementing the VAK-model and deals with a detailed analysis of the learning types distinguished within this model (visual, auditory, and kinesthetic groups of learners). Lexical competence is seen as one of the fundamental aspects for mastering the foreign language skills, especially in writing and speaking. Taking into account the importance of developing lexical competence at school, the paper outlines practical strategies and techniques for applying the VAK-model in the learning process at schools for the development of the lexical potential of pupils. Departing from the experimental implementation of the VAK-model into the learning process, the current study provides the reader with practical guidelines, techniques, and strategies for organising the process of vocabulary acquisition and adjusting it to each personality type.The suggested activities cover all the stages of mastering new vocabulary with a special focus on techniques involving and avoiding translation of lexical units in the stage of semantization of the target vocabulary. Alongside, the possible modifications of the VAK techniques to simultaneously engage several learning types into classroom work and to facilitate the overall process of mastering new vocabulary are considered. Key words: individual learning style, learning type, sensory modalities, auditory learners, visual learners, kinesthetic learners, lexical competence, vocabulary.